Substance use patterns in 9-10 year olds: Baseline findings from the adolescent brain cognitive development (ABCD) study. (1st October 2021) - Lisdahl, Krista M.; Tapert, Susan; Sher, Kenneth J.; Gonzalez, Raul; Nixon, Sara Jo; Feldstein Ewing, Sarah W.; Conway, Kevin P.; Wallace, Alex; Sullivan, Ryan; Hatcher, Kelah; Kaiver, Christine; Thompson, Wes; et al.
Highlights: The ABCD Study® is an open-science, multi-site, prospective study following over 11, 800 9- and 10-year-old youth into early adulthood. At baseline, the majority of the ABCD Study youth reported recently using caffeine (67.6 %) and 22.5 % reported sipping alcohol. The ABCD Study cohort reported little to no use of drugs of abuse (<1% for any drug category) at baseline. Total caffeine use and early alcohol sipping were linked with demographic variables, externalizing behaviors, and parental history of AUD. Aside from caffeine use and early alcohol sipping, the baseline ABCD Study cohort can be considered relatively substance-naïve. Abstract: Background: The Adolescent Brain Cognitive Development ™ Study (ABCD Study®) is an open-science, multi-site, prospective, longitudinal study following over 11, 800 9- and 10-year-old youth into early adulthood. The ABCD Study aims to prospectively examine the impact of substance use (SU) on neurocognitive and health outcomes. Although SU initiation typically occurs during teen years, relatively little is known about patterns of SU in children younger than 12. Methods: This study aims to report the detailed ABCD Study® SU patterns at baseline (n = 11, 875) in order to inform the greater scientific community about cohort's early SU. Along with a detailed description of SU, we ran mixed effects regression models to examine the association between early caffeine and alcohol sipping with demographic factors, externalizing symptoms and parental history of alcohol and substance use disorders (AUD/SUD). Primary Results: At baseline, the majority of youth had used caffeine (67.6 %) and 22.5 % reported sipping alcohol (22.5 %). There was little to no reported use of other drug categories (0.2 % full alcohol drink, 0.7 % used nicotine, <0.1 % used any other drug of abuse). Analyses revealed that total caffeine use and early alcohol sipping were associated with demographic variables (p's<.05), externalizing symptoms (caffeine p = 0002; sipping p = .0003), and parental history of AUD (sipping p = .03). Conclusions: ABCD Study participants aged 9–10 years old reported caffeine use and alcohol sipping experimentation, but very rare other SU. Variables linked with early childhood alcohol sipping and caffeine use should be examined as contributing factors in future longitudinal analyses examining escalating trajectories of SU in the ABCD Study cohort.